Perception of Classroom Activity, Sense of Belonging, and Self-Regulated Learning in Students Taking Online Learning - Amaliyah, Ayu; Yoenanto, Nono Hery; Prihastuti, Prihastuti (Psikostudia : Jurnal Psikologi, 2023)
This study aims to examine the influence of perceptions of classroom activities on self-regulated learning (SRL) through sense of belonging (SoB) as a mediator variable in students who take part in online learning. This urgency arises when students' need for SRL skills becomes important in the implementation of distance learning online. A total of 209 students at universities in Surabaya participated in filling out the online questionnaire. The data was analyzed quantitatively using the Partial Least Square technique. This study used three scales, namely My Class Activities Scale, Perceived Student Belonging Scale, and Online Self-regulated learning Questionnaire (OSLQ). The findings showed that the perception of classroom activity had a significant influence on SRL through SoB as a mediator. Students' perceptions of their classroom activities will influence their feelings of belonging to and connected to their learning institution. Students who are connected to their institution will then tend to manage and organize their own learning. The results of this study have implications for the environmental and social importance in helping students to develop effective SRL strategies.Penelitian ini bertujuan untuk menguji pengaruh persepsi aktivitas kelas terhadap self-regulated learning (SRL) melalui sense of belonging (SoB) sebagai variabel mediator pada mahasiswa yang mengikuti pembelajaran daring. Urgensi ini muncul ketika kebutuhan mahasiswa akan kemampuan SRL menjadi penting dalam pelaksanaan pembelajaran jarak jauh dalam jaringan (daring). Sebanyak 209 mahasiswa di perguruan tinggi di Surabaya berpartisipasi dalam pengisian kuesioner daring. Data dianalisis secara kuantitatif menggunakan teknik Partial Least Square. Penelitian ini menggunakan tiga skala yaitu Skala My Class Activities, Skala Perceived Student Belonging, dan Online Self-regulated learning Questionnaire (OSLQ). Hasil temuan menunjukkan bahwa persepsi aktivitas kelas memiliki pengaruh signifikan terhadap SRL melalui SoB sebagai mediator. Persepsi mahasiswa mengenai aktivitas kelasnya akan mempengaruhi perasaan menjadi bagian dan terhubung dengan institusi belajarnya. Mahasiswa yang terhubung dengan institusinya kemudian akan cenderung mengelola dan mengatur pembelajarannya sendiri. Hasil penelitian ini berimplikasi pada pentingnya lingkungan dan sosial dalam membantu mahasiswa untuk mengembangkan strategi SRL yang efektif.